2011
DOI: 10.4314/afrrev.v5i5.26
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Academic Advising on Academic Performance of University Students in Kenyan Universities

Abstract: Although academic advising in Kenyan universities exists, no

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Also, Pargett (2011) found a relationship between academic advising, student's development, and student satisfaction with college. On the contrary, no significant relationship was found between academic advising and academic performance in the study of Muola et al (2011).…”
Section: Further Related Studiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Also, Pargett (2011) found a relationship between academic advising, student's development, and student satisfaction with college. On the contrary, no significant relationship was found between academic advising and academic performance in the study of Muola et al (2011).…”
Section: Further Related Studiesmentioning
confidence: 62%
“…She stresses that it is essential for the student to keep in touch with the academic advisor until the advising process becomes a professional value. In this regards, the study of Muola et al (2011) recommended that academic advising should actively involve more students.…”
Section: Further Related Studiesmentioning
confidence: 99%
“…Young-Jones et al (2013) found that the frequency of meeting his/her academic advisor leads to students' satisfaction, which in turn contributes to their retention and success. Muola, Maithya, and Mwinzi (2011) suggested that academic advising should actively involve more physical interaction such as a discussion or meeting. Saba'Ayon (2015) suggested that academic advisors should receive intensive training on advising for more positive advising experiences, and hence to improve students' perceptions of academic advising.…”
Section: Significant Difference In Students' Satisfaction Across the Various Demographic Variablesmentioning
confidence: 99%
“…Mentoring has a positive impact on students' ability to deal with stress during study and their success in completing their education at the university (Demir et al , 2014). Students highly value academic advisors who are easy to meet or contact, are friendly, and help in providing direction in connecting their academic experience with future life plans (Muola et al , 2011; Ismail and Jui, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%